Compact SOI Polarization Rotator Using Asymmetric Periodic Loaded Waveguides - Yao Sun; Yule Xiong; Winnie N. Ye (IEEE Photonics Journal, 2016)
We demonstrate the design and experimental results of a silicon-on insulator (SOI) polarization rotator design based on asymmetric periodically loaded waveguides. The rotator design features a compact device footprint of 15.78 $μm$ , with a measured polarization rotation extinction ratio of 11.8 dB at 1525 nm while maintaining at least 6 dB ER over the entire C-band. The fabrication of this rotator is fully compatible with the standard complementary metal-oxide semiconductor (CMOS) process with a SiO2 top cladding. So far, this is the most compact polarization rotator demonstration utilizing the asymmetric periodically loaded SOI waveguides. However, the device is sensitive to fabrication errors; thus, the performance is limited by the current fabrication technology.